Lacosamide in the general population and in people with intellectual disability: Similar responses?. (March 2020) - Allard, Jon; Henley, William; Mclean, Brendan; Sellers, Adrian; Hudson, Sharon; Rajakulendran, Sanjeev; Pace, Adrian; Pashley, Sarah; Maguire, Melissa; Mohan, Monica; Ellawela, Shan; Tittensor, Phil; et al.
Highlights: Lacosamide response in Intellectual Disability (ID) is alike to general population. Efficacy is comparable to similar studies from the UK, Germany & the Netherlands. Higher retention & lower behavioural side-effects noted to Dutch & German studies. Titration differs significantly in first three months between ID and non-ID group. Findings of the UK Ep-ID Register support the safe use of LCM in the ID population. Abstract: Purpose: Epilepsy prevalence is significantly higher in people with Intellectual Disability (ID) compared to people with epilepsy (PWE) from the general population. Increased psychological and behavioural problems, healthcare costs, morbidity, mortality and treatment resistance to antiepileptic drugs (AEDs) is associated with epilepsy in ID populations. Prescribing AEDs for PWE and ID is challenging and influenced heavily by studies conducted with the general population. Our study compares Lacosamide (LCM) response for the ID population to those from the general population; using data from an UK based epilepsy database register (EP ID/PDD AED Register). Methods: Pooled retrospective case notes data for PWE prescribed LCM at 11 UK NHS Trusts were analysed. Participants were classified as per WHO guidance into groups of moderate-profound ID, mild ID and General population. Demographics, concomitant AEDs, starting and maximum dosage, exposure length, adverse effects, dropout rates, seizure frequency were collected. Group differences were reported as odds ratios estimated from univariable logistic regression models. Results: Of 232 consented participants, 156 were from the general population and 76 had ID (24 mild, 52 moderate-profound). Twelve month withdrawal rates and reasons, efficacy, side-effects, start and maximum doses were similar between the groups. Dose titration between baseline and three months was significantly slower in the ID group (p = 0.02). Conclusion: There were no differences for LCM outcomes between general and ID groups. Slower LCM titration in ID populations in the first 3 months was associated with higher retention and lower behavioural side effects as compared to similar European studies.